Editorial for the Gut Microbiota Section - Pramod K. Gopal (Microorganisms, 2025)
The gut microbiota—a diverse and dynamic consortium of trillions of microorganisms inhabiting the gastrointestinal tract—plays a pivotal role in host health across species [...]